Assessment of High Electricity Tariffs on Government Hospitals in Anambra State: Challenges, Cost Implications, Way Forward, and Policy Options for Affordable Energy - Ignatius, Ibekwe Arinze; Akabuike, Josephat Chukwudi; Maryann, Ibekwe Adaobi; Vivian, Nwauzor Chioma; Francis, Ibekwe Chukwubuikem; Akabuike, Nkiru Ugochukwu (Darul Yasin Al Sys, 2026)
The deregulation of the Nigerian power sector and the subsequent 2024 Multi-Year Tariff Order (MYTO) issued by NERC have precipitated a financial crisis for public institutions, as illustrated by the reclassification of government hospitals in Anambra State into “Band A” feeders, which triggered a tariff surge from ₦68/kWh to ₦217/kWh and effectively disregarded the social service nature of healthcare. This study assesses the financial and operational impact of these high electricity tariffs on government hospitals in Anambra State, specifically NAUTH and COOUTH, and validates the observed patterns against national trends. Adopting a mixed-methods research design, the study combines a descriptive cross-sectional survey of 12 key administrative informants with a retrospective cost analysis of energy bills from 2023 to 2024, complemented by a comparative digital verification using internet archives to benchmark local findings against reported energy crises in other tertiary institutions such as UCH Ibadan and LUTH. The findings establish a 230.8% increase in grid energy costs after April 2024; despite the “Band A” service promise, the hospitals still rely on diesel generators for 4–6 hours daily at an average cost of ₦1,400 per liter, resulting in energy expenditures consuming 40–60% of hospital overheads. Internet-based comparative analysis confirms that this represents a systemic national crisis, as peer institutions face the risk of disconnection due to similar debt profiles. The study concludes that the current commercial tariff model is unsustainable for public health parastatals and underscores the need for urgent regulatory and infrastructural responses. It recommends immediate intervention by the Anambra State Electricity Regulatory Commission (ASERC) to implement a subsidized “Social Health Tariff,” alongside a strategic migration to embedded solar-hybrid mini-grids to safeguard energy security and ensure the financial viability of affordable healthcare delivery.